ATIVIDADES DE EXTENSÃO PARA ENTIDADES SEM FINS LUCRATIVOS E PARA EMPREENDIMENTOS DA ECONOMIA SOLIDÁRIA - Basso, Lauri; Brizolla, Maria M. B.; Rauber, Caroline; Didone, Marcelo; Amaral, Simone L. d. (Salão do Conhecimento, 2013)
Resumo